Short Term Stability Testing of Efavirenz-Loaded Solid Lipid Nanoparticle (SLN) and Nanostructured Lipid Carrier (NLC) Dispersions - Pedzisai A. Makoni; Kasongo Wa Kasongo; Roderick B. Walker (MDPI AG, 2019)
The short term stability of efavirenz-loaded solid lipid nanoparticle and nanostructured lipid carrier dispersions was investigated. Hot High Pressure Homogenization with the capability for scale up production was successfully used to manufacture the nanocarriers without the use of toxic organic solvents for the first time. Glyceryl monostearate and Transcutol® HP were used as the solid and liquid lipids. Tween® 80 was used to stabilize the lipid nanocarriers. A Box-Behnken Design was used to identify the optimum operating and production conditions viz., 1100 bar for 3 cycles for the solid lipid nanoparticles and 1500 bar for 5 cycles for nanostructured lipid carriers. The optimized nanocarriers were predicted to exhibit 10% efavirenz loading with 3% and 4% Tween® 80 for solid lipid nanoparticles and nanostructured lipid carriers, respectively. Characterization of the optimized solid lipid nanoparticle and nanostructured lipid carrier formulations in relation to shape, surface morphology, polymorphism, crystallinity and compatibility revealed stable formulations with particle sizes in the nanometer range had been produced. The nanocarriers had excellent efavirenz loading with the encapsulation efficiency >90%. The optimized nanocarriers exhibited biphasic in vitro release patterns with an initial burst release during the initial 0-3 h followed by sustained release over a 24 h period The colloidal systems showed excellent stability in terms of Zeta potential, particle size, polydispersity index and encapsulation efficiency when stored for 8 weeks at 25 °C/60% RH in comparison to when stored at 40 °C/75% RH. The formulations manufactured using the optimized conditions and composition proved to be physically stable as aqueous dispersions.